PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING BERBASIS TPACK TERHADAP HASIL BELAJAR PPKN DI MADRASAH IBTIDAIYAH SWASTA - Amanda Fathin Furroyda; Hamidulloh Ibda; Andrian Gandi Wijanarko (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2022)
The learning outcomes of grade III students in Civic Education (PPKn) subjects are still low. The cause of the low learning outcomes is that the methods used by teachers are still conventional, namely with lecture methods and using single learning resources. Learning also has not utilized technology in the learning process. To improve the results of these students, researchers used the Contextual Teaching and Learning (CTL) learning model. This study uses a quasi-experiment research model with a nonequivalent control group design. The study results concluded that the TPACK-based CTL learning model affects the learning outcomes of PPKn class III. It is evidenced by the results of the t-test conducted by researchers using the SPSS application. In cognitive learning outcomes, a significant value of 0.004 < 0.05 was obtained, based on the conditions of concluding if the significant value < significant level, Ha was accepted, and H0 was rejected. It was concluded that the TPACK-based CTL learning model affects the cognitive learning outcomes of PPKn class III. While in the affective learning outcomes of students, a significant score of 0.049 <0.05 was obtained, it can be concluded that the TPACK-based CTL learning model affects the affective learning outcomes of PPKn class III Madrasah Ibtidaiyah Salafiyah Kranggan